Deployment of Agriculture 4.0 with the Integration of IoT - Sheila Maria Muniz (Computational Algorithms and Numerical Dimensions)
Agriculture is the primitive and crucial occupation for the people. Smart Agriculture (SA) is an emerging concept, because IOT sensors are capable of providing information about agriculture fields and then act upon based on the user input. Urbanization, which indirectly affected the lives of people in the agricultural sector by increasing level of environmental pollution, climate change, degradation of soil and water quality, increasing population, decreasing income from the farming industry, etc. In this Paper, it is proposed to develop a SA System that uses advantages of cutting-edge technologies such as Arduino, IOT and Wireless Sensor Network (WSN). Internet of Things (IoT)-based smart sensors is the new technique for the SA system. IoT-based SA system consists of various sensor nodes placed in different locations, internet service, smart remote devices, or computer systems with the internet that monitor the operation of sensor nodes, Wi-Fi, a camera with a microcontroller, and different interfacing sensing nodes for service. The system has a duplex communication link based on a cellular-Internet interface that allows for data inspection and irrigation scheduling to be programmed through an android application.